Production, Purification And Characterization Of Thermostable Lipase From An Extremophilic Bacillus Subtilis Ns 8 - Olusesan, Akanbi Taiwo (2010)

(untitled)
Lipase is one of the most versatile biocatalysts and has a wide biotechnological application particularly in the production of functional lipids. This work aimed at producing, purifying and characterizing thermostable lipase from an extremophilic Bacillus subtilis NS 8 isolated from Setapak hotspring. Lipase production by an extremophilic Bacillus strain which has been previously identified by phenotypic methods and confirmed by the beneficial genotypic techniques of 16S rRNA sequence analysis as Bacillus subtilis was carried out. Optimization of the culture conditions which are; nutritional (carbon, nitrogen and mineral sources) and physical (temperature, pH and agitation) conditions was conducted using the conventional shake-flask system. It was observed that the most suitable components of UPLOAD the basal medium for the lipase production were 2.5% Olive oil (carbon); 1.5% Peptone (nitrogen) and 0.1% MgSO4.7H2O (mineral) at an optimum temperature of 50°C, pH 7.5 and 150 rpm agitation, giving an enzyme yield of 4.23 U/ml from the original yield of 2.48 U/ml. Statistical optimization using Response Surface Methodology (RSM) was carried out. An optimum lipase production of 5.67 U/ml was achieved when olive oil concentration of 3%, peptone 2%, MgSO4.7H2O 0.2% and agitation rate of 200 rpm were combined. Lipase production was further carried out inside a 2 L bioreactor with a 1.5 L working volume which yielded an enzyme activity of 14.5 U/ml after 15 hours of incubation. Crude lipase produced was purified by ultrafiltration, DEAE – Toyopearl 650M and Sephadex G-75 column. The enzyme was purified 500-fold with a recovery of 16%. The purified enzyme showed a prominent single band on SDS–PAGE and its molecular weight was determined to be 45 kDa. The optimum pH and temperature for activity of lipase were 7.0 and 60°C. The enzyme was stable in the pH range 7.0 – 9.0 and temperature range 40 – 70°C. It showed high stability with half lives of 273.38 min at 60°C, 51.04 min at 70°C and 41.58 min at 80°C. The D-values at 60, 70 and 80°C were 788.70, 169.59 and 138.15 min respectively. The enzyme’s enthalpy, entropy and Gibb’s free energy were in the range of 70.07 to 70.40 KJmol-1, -83.58 to -77.32 KJmol-1 K-1 and 95.60 to 98.96 KJmol-1 respectively. It was stable in presence of divalent metal ions like Mg2+, Ca2+ and markedly inhibited by Zn2+, Cu2+ and Fe2+. The enzyme was able to hydrolyze most of the natural oil tested, with the highest hydrolytic activity on soy bean oil. On TLC plate, the enzyme was non-regiospecific as it showed random positional specificity for triolein hydrolysis.